Geosynchronous Magnetopause Crossings and Their Relationships With Magnetic Storms and Substorms - A. A. Samsonov; Y. V. Bogdanova; G. Branduardi‐Raymont; L. Xu; J. Zhang; D. Sormakov; O. A. Troshichev; C. Forsyth (Space Weather)
Abstract The paper investigates the strengthening of magnetospheric activity related to geosynchronous magnetopause crossings (GMCs). We make a list of GMC events using the empirical magnetopause model (Lin et al., 2010, https://doi.org/10.1029/2009ja014235) and hourly averaged OMNI data and find which solar wind and magnetospheric conditions accompany and follow the GMCs. The GMCs are mostly caused by the impact of interplanetary coronal mass ejections (ICMEs) and/or interplanetary shocks often with a strong increase in the density and a moderate increase in velocity. The average solar wind density during the first GMC hour is higher than 20 cm−3 in 70% cases, while the velocity is higher than 500 km/s in 56% cases. The hourly interplanetary magnetic field (IMF) BZ is negative in 87% cases. The average over all events SMU (SML), Kp, and PC indices reach maxima (minima) in 1 h after the GMC beginning, while the delay of the minimum of the Dst index is usually 3–8 h. These average time delays do not depend on the strength of the storms and substorms. The SML (Dst) minimum is less than −500 nT (−30 nT) in the next 24 h in 95% (99%) cases, that is, the GMC events are mostly followed by magnetic storms and substorms. We compare solar wind and magnetospheric conditions for GMCs connected with ICMEs and stream interaction regions (SIRs). Our study confirms that the ICME‐related events are characterized by stronger ring current and auroral activity than the SIR‐related events. The difference might be explained by the different behavior of the solar wind velocity.